Review and Comparison of Routing Metrics in Cognitive Radio Networks - Alaleh Asghary Astaneh; Solmaz Gheisari (Emerging Science Journal, 2018)
In this paper, cognitive radio network is briefly introduced as well as routing parameters in cognitive radio networks. Due to lack of Spectrum, using not efficient methods of allocating static spectrum, in cognitive radio networks dynamic accessing spectrum is functional. Utilizing opportunistic a Spectrum requires recognition of routing parameters and metrics in cognition radio networks, which means considering fulfilling the minimum requirements of quality of service (QOS) secondary users need to use the allowed range of primary (main) users. Since primary users are prior to use the spectrum, when primary and secondary users coexist, they need to monitor the bandwidth of the authorized spectrum. One of the most important stages to excess the dynamic spectrum is to explore it. Detection of the presence of the authorized users by unauthorized users is one of the things done in this stage, which is called spectroscopy. In the next stage, we used the analyzed information I was spectroscopy, to decide on accessing the spectrum. cognition radio is defined as a smart wireless communication system, which is aware of the environment and changes its job variables like power forward, type of modulation, carrier frequency etc. using environment learning. For further explaining routing metrics, we try to compare routing metrics in cognitive radio networks and wireless network and analyze its challenges in one-way routing and in multi-route routing.